Pengaruh Kualitas Pelayanan, Kepercayaan, dan Citra Lembaga terhadap Kepuasan Nasabah LPD Desa Adat Tulikup Kaler Gianyar - I Kadek Sara Mandiyasa; I Made Sumartana; I Kadek Aditya Pratama; I Made Kartika (Universitas Ngurah Rai, 2026)
Customer satisfaction is regarded as an important benchmark for assessing a financial institution's ability to maintain sustainable relationships with its customers. This condition is influenced by several factors, particularly service quality, trust, and corporate image. The presence of issues related to service consistency and information delivery at LPD Desa Adat Tulikup Kaler Gianyar provided the rationale for conducting this study. The research was designed to examine the effects of service quality, trust, and corporate image on customer satisfaction, both collectively and individually. A quantitative approach was employed, and data were collected from 90 respondents selected through purposive sampling. The findings indicate that service quality, trust, and corporate image contribute to customer satisfaction both simultaneously and partially, with corporate image demonstrating the strongest contribution.